Pengembangan Sistem Informasi Pengelolaan Keuangan Yayasan Berbasis Website (Studi Kasus: Yayasan Pendidikan Islam Bhakti Pertiwi Kulon Gresik) - Aruf Rachman Hakim; Buce Trias Hanggara; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Bhakti Pertiwi Kulon Islamic Education Foundation (YPI BP Kulon) is a foundation built to teach Al-Qur'an education and provide social assistance to the community in Gresik City. Financial management at YPI BP Kulon is still carried out on bookkeeping and then transferred to Microsoft Excel and Word every year. The financial records were copied back on a piece of paper more concisely by the treasurer before being transferred, and the transfer process was also assisted by someone else. Bookkeeping is also still separate between each treasurer which can lead to double recording. The formulation of the problem in this study is how to build an information system that makes it easier to manage records and make financial reports. The purpose of this research is to make it easier to manage records and make financial reports. The problem is solved by building a financial management information system using the waterfall model. This study concludes that the problems in YPI BP Kulon are facilitated by reducing and improving current business processes (as-is) to produce recommendation (to-be) business processes by utilizing an information system built using the Laravel framework. User acceptance testing (UAT) testing is then carried out to determine the level of user acceptance of the information system. The results obtained to produce a value of 88.64% which indicates that the user strongly agrees with the system that has been developed.